2013
DOI: 10.1016/j.jpubeco.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Biased perceptions of income distribution and preferences for redistribution: Evidence from a survey experiment

Abstract: Individual perceptions of income distribution play a vital role in political economy and public finance models, yet there is little evidence regarding their origins or accuracy. This study examines how individuals form these perceptions and posits that systematic biases arise from the extrapolation of information extracted from reference groups. A tailored household survey provides original evidence on the significant biases in individuals' evaluations of their own relative position in the distribution. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
377
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 604 publications
(461 citation statements)
references
References 56 publications
26
377
1
17
Order By: Relevance
“…That inequality is generally supported by those advantaged and opposed by those disadvantaged is clearest when looking at the change in attitudes when people who think that they are the beneficiaries of inequality discover that inequality actually harms them in some way. Finding out that one is not as advantaged as one imagined oneself to be increases people's worry about income inequality (Kuziemko, Norton, Saez, & Stantcheva, 2015) and increases their support for policies that ameliorate inequality (Cruces, Perez-Truglia, & Tetaz, 2013).…”
Section: Psychological Correlates Of Income Inequality: Lower Life mentioning
confidence: 99%
“…That inequality is generally supported by those advantaged and opposed by those disadvantaged is clearest when looking at the change in attitudes when people who think that they are the beneficiaries of inequality discover that inequality actually harms them in some way. Finding out that one is not as advantaged as one imagined oneself to be increases people's worry about income inequality (Kuziemko, Norton, Saez, & Stantcheva, 2015) and increases their support for policies that ameliorate inequality (Cruces, Perez-Truglia, & Tetaz, 2013).…”
Section: Psychological Correlates Of Income Inequality: Lower Life mentioning
confidence: 99%
“…Moreover, a number of recent empirical contributions in psychology and economics have shown that the perception of inequality reported by people in opinion surveys does not correspond to income inequality as it is commonly measured (Norton and Ariely, ; Cruces et al ., ; Verme, ; Chambers et al ., ; Gimpelson and Treisman, ). Other contributions have shown that a society's structure can be perceived to be considerably less equitable than it actually is (Niehues, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mollerstrom et al (2015) conduct a survey experiment in Sweden and inform a treatment group about their true relative position, thereby exogenously (but truthfully) manipulating perceptions of relative income. They show that this causes changes in individual demand for redistribution and that the direction of these changes indicate that a substantial fraction of people do exhibit the theoretically proposed negative correlation between (perceived) relative income and demand for redistribution (see also Cruces et al, 2013, for evidence corroborating this conclusion).…”
Section: Underlying Factors That Shape Demand For Redistributionmentioning
confidence: 84%